Pengaruh Beban Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Bank Bengkulu Cabang Manna - Habibullah Al Haj Al Haddad; Ahmad Soleh; Yudi Irawan Abi (Universitas Dehasen Bengkulu, 2023)
The purpose of this study was to simultaneously determine the performance burden and work discipline on the performance of Bengkulu Manna branch bank employees and to determine which faktors were the most dominant influencing either partially or simultaneously.The sample in this study was 40 employees at the Bengkulu Manna branch of the bank. Sampling using the total sampling method, namely the entire population of members who will be mandated as a sample because large samples tend to give or are closer to the true value of the population or it can be said that the error is smaller (deviation from the population value). In order to be more efficient in obtaining respondent data, the researcher using questionnaire data. Data analysis techniques in the form of numbers and calculations using statistical methods, then the data must be classified in certain categories using the SPSS (Statistical Package for Social Sciences) program.Based on the results of multiple linear regression, the equation Y=6.199 -336 X1 - 0.813 X2 is obtained. The results of the research and the workload hypothesis show that t count > t tabel, namely (-3.164> 2.02809) and sig < a (0.000 < 0.050). Work Discipline X2 , shows t arithmetic > t tabel, namely (5.079> 2.02809) and sig < a (0.000 < 0.050). Simultaneously, workload and work discipline variabels have a significant effect on employee performance. Partially, the two variabels of workload and work discipline have a significant effect on employee performance.